Evaluation of Octo Mobile User Experience using the System Usability Scale Method - Andre Gunakusuma Fergo; Chanifah Indah Ratnasari (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
In order to improve the quality of the Octo Mobile by Bank Cimb Niaga application, it is necessary to carry out usability testing of the application using the System Usability Scale (SUS) with a Likert scale for the answer. The purpose of this study is to evaluate usability and analyze user experience on the Octo Mobile application, so that it is expected to be used as a reference for application development by Bank CIMB Niaga. Respondents consisted of 39 Octo Mobile application users. Testing was carried out by directly interviewing respondents and filling out a questionnaire containing 10 statements. The results of testing with the SUS method obtained a result of 58.5%. Based on these results, the acceptability of the Octo Mobile application is in the marginal low range, the adjective rating is in the OK level, and the grade scale is in class F. Based on these results it can be concluded that the Octo Mobile application has usability that is acceptable to users, but still needs to be improved and further upgrades.